THE CORRELATION BETWEEN INTRINSIC MOTIVATION AND ENGAGEMENT IN PEER-ASSISTED LEARNING AMONG FIRST-YEAR MEDICAL STUDENTS - Yoana, Eggi Hevryka; Puspadewi, Natalia; Juliawati, V. Dwi Jani; Anastasia, Gisella (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2025)
Background: Student-centered approaches are essential in medical education. Peer-Assisted Learning (PAL) is an example of an active participative learning process that enhances engagement, while intrinsic motivation is a key factor influencing student participation. This study investigates the correlation between intrinsic motivation and engagement among preclinical medical students in PAL sessions. Aims: This study investigates the correlation between intrinsic motivation and engagement among preclinical medical students in PAL sessions.Methods: A cross-sectional observational design was employed with 136 first-year FKIK UAJ students who met the inclusion criteria. Intrinsic motivation was assessed using the intrinsic motivation subscale of the Situational Motivation Scale (SIMS), and students’ engagement was evaluated using a 7-point Likert scale questionnaire by Kassab et al., which covered emotional, behavioral, and cognitive dimensions of students’ engagement. Data were collected online and analyzed with Spearman and Pearson correlation tests.Results: Students exhibited high intrinsic motivation (6.13 ± 0.82) and engagement levels: emotional (6.07 ± 0.90), behavioral (6.33 ± 0.68), and cognitive (5.53 ± 0.93). Positive correlations were found between intrinsic motivation and emotional (rs = 0.797; p < 0.001), behavioral (rs = 0.539; p < 0.001), and cognitive engagement (r = 0.607; p < 0.001).  Conclusion: Students with high intrinsic motivation tend to engage in PAL, especially on the emotional dimension. This suggests that fostering intrinsic motivation may enhance student engagement in PAL sessions, particularly at the emotional level, which subsequently improves their learning experiences.